Strategi Guru Pendidikan Pancasila dalam Menanamkan Nilai Pancasila melalui Pembelajaran Kontekstual di SMP Negeri 1 Paguyangan - M Lutfi Baehaqi; Mieke Mindyasningrum; Eky Risqiana; Yogi Ageng Sri Legowo (Universitas Negeri Gorontalo, 2026)
A contextual approach to learning emphasizes the effort to connect instructional content with the realities of students’ lived experiences. Through this approach, students are encouraged to integrate the knowledge they acquire with their everyday experiences, making the learning process more relevant, meaningful, and applicable to real-life situations. This study employed a descriptive qualitative approach to explore in depth how Pancasila Education teachers implement strategies to instill Pancasila values through learning activities oriented toward real-life contexts. Data were collected through direct observation and interviews. The data were then analyzed systematically through the stages of filtering, organizing, and interpreting information to obtain a comprehensive understanding of classroom learning practices and teachers’ efforts to strengthen students’ understanding of Pancasila values. The findings indicate that teachers implement strategies for instilling Pancasila values through a comprehensive learning approach that is contextually relevant and grounded in students’ real experiences. In this process, teachers do not merely focus on students’ cognitive understanding of concepts but also integrate affective and psychomotor aspects. Consequently, learning activities contribute to the holistic development of students’ attitudes, character, and social skills. Overall, the strategies employed by Pancasila Education teachers to instill Pancasila values through contextual learning include role modeling, habituation, group work, collaboration, deliberation, and the distribution of responsibilities